2004
DOI: 10.1097/01.aog.0000104060.37475.29
|View full text |Cite
|
Sign up to set email alerts
|

Is Discordant Growth in Twins an Independent Risk Factor for Adverse Neonatal Outcome?

Abstract: Discordance places twins at increased risk for some adverse perinatal outcomes, whether they are AGA or SGA. Discordance was not an independent risk factor for serious neonatal morbidity or mortality; however, this study was underpowered to detect those differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
2
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 13 publications
3
72
2
7
Order By: Relevance
“…This risk factor or more frequent maternal complications might be the reason for the higher incidence of cesarean delivery in discordant twins. In the studies of Cheung et al 6 and Amaru et al, 23 caesarean delivery rates were higher in highly discordant twins, too.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This risk factor or more frequent maternal complications might be the reason for the higher incidence of cesarean delivery in discordant twins. In the studies of Cheung et al 6 and Amaru et al, 23 caesarean delivery rates were higher in highly discordant twins, too.…”
Section: Discussionmentioning
confidence: 86%
“…Patterson et al 22 also found that adverse neonatal outcome was associated with IUGR, birth weight percentile and prematurity, but not discordance. In the study of Amaru et al, 23 discordant twins were at risk for some adverse neonatal outcome like LBW and VLBW birth, NICU admission, neonatal oxygen requirement and hyperbilirubinemia; whether they were AGA or SGA. In that study, discordance did not appear to be an independent risk factor for neither serious neonatal morbidity nor mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Most authors believe that 25% is the difference level above which discordance should be considered as abnormal and might reflect some significant degree of growth restriction (Blickstein & Keith, 2004). Our study evaluates neonatal morbidity and mortality along several degrees of weight discordance in twin pregnancies, excluding cases with associated fetal abnormalities and TTTS that might have biased results of previous investigations (Copperstock et al, 2000;Amaru et al, 2004). We did not find any maternal factor that may be related to discordant growth in twins as it was previously reported (Hartley et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…In retrospective studies the threshold range from 10 to 30% [4,5,9,[19][20][21][22][23][24] (Table 1). According to the American College of Obstetricians and Gynecologists [27] an EFW disparity of approximately 15-25% is considered to be clinically significant, whereas the UK National Institute for Health and Care Excellence guidelines [28] set the threshold at the level of 25% and recommend the referral of such pregnancies to a tertiary fetal medicine center.…”
Section: Estimated Fetal Weight Discordance and Perinatal Outcomementioning
confidence: 99%